Sistem Pendidikan Di Negara China - Fariha Fariha; Komarudin Sassi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Education is a window of knowledge that is beneficial for everyone. High and low levels of education are very important to a country's economic growth. Importantly, take advantage of a country's competitiveness. Based on some evidence the country of China became one of the countries that had the best education in the world. China has a trans-centralized education system, meaning that it starts from the central, provincial, municipal, district level, and includes regional autonomous regions. Then education in China consists of four sectors (1) basc education, (2) technical & vacational education, (3) higher education, and (4) adult education. In addition to these four sectors there are also non-formal education, namely literacy education in order to eradicate illiteracy. The educational curriculum in China is more flexible with the needs of its students and the welfare of teachers being given more attention.